Therapy of pathology secretory disease of the breast - G. Kh. Khanafiev; S. A. Berzin; S. M. Demidov (ABV-press, 2016)
Pathogenesis of serous discharge from the nipples of the breast is complex and includes the following components: hormonal imbalance as a backdrop, stimulating increased secretion in the ducts of serous content, resorption of the liquid component of a secret, resulting in local pathological effects of protein resorption, hormone content, autoimmune reactions ductless with subsequent development of proliferative processes in them. Under adverse conditions, infection occurs from an external or internal source of microorganisms. The presence of fluid in the ducts, mammary system ductal communication with the external environment, is an "open gate" for content ductal infection of the mammary glands. This creates the prerequisites for the development of proliferative processes in the first phase of the inflammatory origin. Application of 194 women with serous secretions from the nipples of the breast combined combinations of enzymes, glucocorticoids, progestogens, gonadoliberins and other agonists, suppress the proliferation of drugs that helped to put an end to abnormal secretion and prevent changes in the walls of the ducts and periductal breast tissue at different stages of disease.